Planificación Estratégica para la Cooperativa de Ahorro y Crédito 29 de Enero en el Cantón Chaguarpamba Provincia de Loja periodo 2017 – 2022 - Hidalgo Chamba, Sonia Yaneth (2017)
The present work is a prescriptive research. The starting point was the determination of the objectives of the study, being the following; To carry out strategic planning as a general objective and within the specific objectives to carry out an economic economic diagnosis and to determine strategies, activities and budget for said cooperative, the same ones that marked the route of the procedures, actions and analysis of the present work. The core of the work consisted of the external analysis, from which the necessary information was obtained to elaborate the matrix EFE (matrix of evaluation of external factors), as well as the realization of the matrix of the competitive profile MPC. The analysis of the internal factors was carried out, for which the surveys were applied to both the internal and external actors and the financial diagnosis with the application of the vertical and horizontal financial analysis, application of indicators PEARLS; The information obtained served as a basis for the elaboration of the EFI matrix (matrix for the evaluation of internal factors). With the information obtained through the analysis of both external and internal factors, the SWOT matrix was elaborated and, from the technical conjugation of the FO - FA - DO - DA crosses, Strategies for that entity; In order to determine the position of the strategy profile for the cooperative, the strategic position matrix and evaluation of PEYEA actions were applied and the MPEC quantitative strategic planning matrix was completed, through which it was possible to classify, identify and select in order the strategies for the entity. The structure of the strategic objectives is nuanced by the determination of Strategy, Activities, Policy, Lines of Action, Resources, Time, Responsible for its fulfillment, Expected Results, Financing, Development and Budget. In the complementary part of this thesis work, the conclusions are made with the respective recommendations, which generate an important contribution in the research carried out. The following work was applied in a population of 2072 where a sample of 324 people was determined to obtain the information was done through the survey. The work was concluded: The delinquency indicator allowed to identify weaknesses in collection management, concluding that there is inefficiency in the credit assessment, ie the analysis of the applicant's income, verification of information and lack of guarantees, It is for this reason that the delinquency of the credits granted are above the level of what is established in the Cooperativist system; Therefore, it is recommended to apply a policy of restructuring expired loans that allows dialogue with partners by offering facilities in their payments and longer terms in order to achieve liquidity and economic solvency.